2020
DOI: 10.1002/aoc.5988
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antifungal and antibacterial activities evaluation of copper (II), zinc (II) and cadmium (II) chloride and bromide complexes with new (E)1‐(3,4‐dimethoxybenzylidene)‐4‐methylthiosemicarbazone ligand

Abstract: The reactions of Cu (II), Zn (II) and Cd (II) chloride or bromide with (E)‐1‐(3,4‐dimethoxybenzylidene)‐4‐methylthiosemicarbazone (MTSVT) lead to the formation of new complexes. They were characterized by spectroscopic studies: IR, 1H and 13C NMR. The crystal structures of the compounds [MTSVT] (L), [ZnBr2(MTSVT)2] (2), [CdCl2(MTSVT)2] (3) and [CdBr2(MTSVT)2.H2O] (4) were determined by X‐ray diffraction. For complexes 2–4, the ion is coordinated through the sulfur atom. All compounds were tested for their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…The conversion of the aldehyde groups, in Ald-ZIFs, to imine groups in TSC-ZIFs, was further conrmed by the strong band at 1604 cm À1 corresponding to the C]N stretching vibration. 70 Two new IR bands are also observed at 1047 and (1864) cm À1 , indicative of the presence of the thiosemicarbazone group corresponding to the n(C-N) and n(C]S) stretching vibrations, respectively (Fig. S1 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of the aldehyde groups, in Ald-ZIFs, to imine groups in TSC-ZIFs, was further conrmed by the strong band at 1604 cm À1 corresponding to the C]N stretching vibration. 70 Two new IR bands are also observed at 1047 and (1864) cm À1 , indicative of the presence of the thiosemicarbazone group corresponding to the n(C-N) and n(C]S) stretching vibrations, respectively (Fig. S1 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason may be due to the complexation of ligand to zinc center in PS@MOF, which has an influence on the formation of sclerotia. The previous literature studies also reported that the complexation of ligand to zinc center led to enhancement of antibacterial/antifungal activity. , …”
Section: Resultsmentioning
confidence: 92%
“…The previous literature studies also reported that the complexation of ligand to zinc center led to enhancement of antibacterial/antifungal activity. 39,40 In order to explore the broad spectrum of photodynamic antifungal activity of PS@MOF, two other plant fungi, P. aphanidermatum and B. cinerea, were also treated with PS@ MOF at concentrations 50, 100, 200 mg L −1 . The results showed that PS@MOF had much better control efficiency under light irradiation than that under dark conditions, which indicated that PS@MOF had similar photodynamic antifungal activity against P. aphanidermatum and B. cinerea (Figures 4a,b and S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13 C NMR (DMSO-d 6 ) δ: 31, 56, 109, 111, 122, 127, 142, 149, 151, 177. IR cm −1 : 3351, 2990, 1601 [ 46 ]. LC-QTOF HRMS ( m / z ): calculated monoisotopic mass: 253.0885, measured monoisotopic mass: 253.0889.…”
Section: Methodsmentioning
confidence: 99%